On the Roots of Difficulties in Learning about Cell Division: Process-based analysis of students' conceptual development in teaching experiments - Riemeier, Tanja; Gropengießer, Harald (International journal of science education, 2008)
Empirical investigations on students' conceptions of cell biology indicate major misunderstandings of scientific concepts even after thorough teaching. Therefore, the main aim of our research project was to investigate students' difficulties in learning this topic and to study the impact of learning activities on students' conceptions. Using the Model of Educational Reconstruction, a four-phase design was carried out. Firstly, there was the clarification of science subject matter. Secondly, students' conceptions were investigated, and finally, the learning activities were designed. An evaluation of these learning activities was carried out using five teaching experiments, each with three 9 th grade students (15-16 years, Grammar school). Interpretation of students' "pathways of thinking" and their conceptual change during instruction was framed theoretically by experiential realism. Theoretical framework, methods and outcomes of the study may contribute to a deeper understanding of students' ways of thinking in the field of cell biology and reveal the process of conceptual development by using well planned learning activities.